Disharmonisasi Aturan Hukum Bank Tanah Dan Reforma Agraria - Putra, Ido Gustiawan; Azzahra, Mutiara; Prakoso, Bhim; Efendi, Aan (Universitas Medan Area, 2025)
This paper aims to analyze how the harmonization of land bank law and land law provisions in agrarian reform. This study is a normative legal research that examines the harmonization of land bank law and land law provisions in Indonesia. This research uses a statute approach to find the harmonization of land bank legal rules through Law Number 13 of 2022 concerning the Formation of Legislation. This research uses data from Law No. 63 of 2023 on Job Creation, Government Regulation No. 64 of 2021 on the Land Bank Agency, Law No. 5 of 1960 on Basic Agrarian Principles, and MPR Decree No. IX of 2001 on Agrarian Reform. The data is processed by analyzing the harmonization of the legal rules of the land bank and the provisions of land law in agrarian reform through Law Number 13 of 2022 concerning the Formation of Legislation. The results of this study show that the land bank regulated in the provisions of Law No. 63 of 2023 on Job Creation and Government Regulation No. 64 of 2021 on the Land Bank Agency is disharmonious with the 1945 Constitution, Law No. 5 of 1960 on Basic Agrarian Principles, and MPR Decree No. IX of 2001 on Agrarian Reform.